Exploring the use of learning contracts for language learning - Ismail, Normah; Md. Yusof, Masdinah Alauyah (2008)
Although the concept of learning contracts is not new, it is only recently that the potential of this strategy has been recognized at the tertiary level education. It has gained some interest among language educators to use it as a way to encourage learners to be more involved in their learning. The rationale for using learning contracts in this study is based on the view that the learning contract allows the students to structure their own learning and become active participants in the educational process. Positive outcomes from recent studies reaffirmed that the learning contract is worth investigating as a strategy for promoting autonomy in language learning. This paper will explore the viability of using learning contracts among undergraduate language learners. First, it will examine the relationship between learning contracts, the attributes of resourcefulness and independent learning in developing autonomous language learners. Next, it describes the pilot study that was undertaken at a City Campus. Lastly, it will discuss the implications if language learning contracts are implemented at tertiary level.